Szymon Musaeus's speech on the occasion of the introduction of Matthias Breu to the position of the rector of the Toruń Gymnasium in 1568 from the collection of the Provincial Public Library – the Copernicus Library in Toruń - Dreikopel, Tomasz (Folia Toruniensia, 2025)
The study includes an introduction, explanations, transliteration of the Latin text and the first full translation of the speech delivered on 8 March 1568 by Pastor Szymon Musaeus, Doctor of Theology, Honorary Professor at the Toruń Gymnasium and then head of the local Protestant clergy, on the occasion of the induction of magister Matthias Breu, to the position of the rector. Musaeus's speech remains a valuable historical source that shows the backstage of the establishment of the Gymnasium in Toruń.